Computed tomography densitometric study of anti-angiogenic effect of regorafenib in colorectal cancer liver metastasis. (13th February 2018) - Reginelli, Alfonso; Clemente, Alfredo; Cardone, Claudia; Urraro, Fabrizio; Izzo, Andrea; Martinelli, Erika; Troiani, Teresa; Ciardiello, Fortunato; Brunese, Luca; Cappabianca, Salvatore
Aim: Regorafenib induces radiological changes in liver metastasis among patients with metastatic colorectal cancer (mCRC). The standard criteria used to evaluate solid tumor response (Response Evaluation Criteria in Solid Tumors) may be limited in assessing response to biologic agents with anti-angiogenic action.Patients & methods: A total of 67 hepatic lesions in 32 selected patients were analyzed to evaluate tumor attenuation as measured by Hounsfield unit (HU) and size changes.Results: Following two cycles of regorafenib, tumor HU values decreased in the in 73.1% (49/67) of lesions (average HU changes -25.6%) while tumor size increased in 64.2% (43/67) of them (average size changes +25.4%).Conclusion: The computed tomography density changes evaluation may be an additional tool, in combination with tumor sizing, to evaluate tumor response in patients treated with regorafenib.